Effect of Surfactant on Single Drop Mass Transfer in Liquid-Liquid Extraction - Panut Mulyono; Setia Muliati (ASEAN Journal of Chemical Engineering, 2007)
iquid-liquid mass transfer coefficients for single freely rising drops in the presence of surfactant in an extraction column have been investigated using the system of kerosene-acetic acid-water. The surfactant used in this study was alkyl benzene sulfonate (ABS). The experiments were carried out by bubbling kerosene-acetic acid solution as a series of single drops from the bottom of a column containing water-ABS solution. The column used in this experiment was made from glass of 36 mm inside diameter and constructed of 60, 120, and 180 cm height. The effects of surfactant concentration, column height, and drop diameter on the overall mass transfer coefficient have been studied. The data can all be correlated by Shd = 2.08 x10−5 Red 4.01 We −1.97 (dd / H ) 0.68 with an average deviation of 17.72%. This equation is valid for the ranges of Red from 186.68 to 402.19, We from 0.80 to 3.33, and dd/H from 0.0028 to 0.0105.